Italian trade unions: Still shifting between consolidated organizations and social movements? - Ida Regalia (Management Revue, 2012)
This article discusses the current characteristics of trade unionism in Italy. First, however, attention is paid to the initial imprinting of the model, which stemmed from the circumstances in which the trade unions were reconstituted at the end of WWII, and whose far-reaching consequences are still apparent today. In fact, because of original divisions along ideological lines, and within a context of enduring voluntarism and low institutionalisation, the Italian trade unions, which acquired large followings and strong organizational capacity and influence over time, still tend to oscillate between behaving as either organizations or social movements according to convenience and to pressures applied by the rank and file.
Keywords: D72; J50; J51; 650; trade unions; social movements; political processes; Italy